CHARACTERIZATION THE ALLERGENICITY AND STABILITY OF ALLERGENS OF FRESHWATER SNAIL, Pomacea canaliculata (Jurnal Teknologi (Sciences & Engineering), 2024)
Snail allergy is considered a serious form of food allergy with prevalence of 1.4 to 22% worldwide. However, allergy to Pomacea canaliculata, a commonly consumed local snail has not been well-described. Hence, this study aimed to characterize the allergenicity and stability of the allergenic proteins of P. canaliculata by proteomics approach. Snail flesh was treated with several thermal and non-thermal treatments prior to overnight protein extraction. The snail proteins were then subjected to SDS-PAGE, followed by immunoblotting, two-dimensional electrophoresis (2-DE), 2-DE immunoblotting and mass-spectrometry analysis. Raw snail demonstrated 31 protein bands between 10 to 250 kDa, with fewer protein bands in treated snails. Boiled snails had the most protein bands among thermally treated snails, while salted and dried snails showed more bands than pickled snails among non-thermal treatments. Immunoblotting of raw extract demonstrated 16 IgE-binding bands, with the 33 and 42 kDa protein bands were identified as the major. The 33 kDa allergen was highly stable to all treatments applied, while the 42 kDa was sensitive to thermal and pickling treatments. Fewer allergenic bands were present in treated snails, with allergenicity ranked as raw > boiled > roasted > fried for thermal treatments, and raw > salted > dried > pickled for non-thermal treatments. Mass spectrometry identified the 33 kDa and 42 kDa allergens as tropomyosin and actin, respectively. In conclusion, P. canaliculata has numerous allergenic proteins with varying stability.